2016
DOI: 10.1038/bjc.2016.376
|View full text |Cite
|
Sign up to set email alerts
|

Loss of KCNQ1 expression in stage II and stage III colon cancer is a strong prognostic factor for disease recurrence

Abstract: Background:Colorectal cancer (CRC) is the third most common cancer worldwide. Accurately identifying stage II CRC patients at risk for recurrence is an unmet clinical need. KCNQ1 was previously identified as a tumour suppressor gene and loss of expression was associated with poor survival in patients with CRC liver metastases. In this study the prognostic value of KCNQ1 in stage II and stage III colon cancer patients was examined.Methods:KCNQ1 mRNA expression was assessed in 90 stage II colon cancer patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 55 publications
1
31
1
Order By: Relevance
“…In contrast, no direct association between hypomethylation and higher gene expression could be concluded in the CpG site cg23750514 located in the KCNQ1 gene. Contrary to our finding, that hypomethylation is associated with poor prognosis in patients with non-metastatic CRC, the loss of KCNQ1 mRNA and protein expression in stage II and III colon cancer has been proposed as a prognostic factor for poor disease-free survival 42. Additionally, another report showed that low expression of KCNQ1 protein was significantly associated with poor OS in patients with CRC with liver metastases after hepatic resection 43.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, no direct association between hypomethylation and higher gene expression could be concluded in the CpG site cg23750514 located in the KCNQ1 gene. Contrary to our finding, that hypomethylation is associated with poor prognosis in patients with non-metastatic CRC, the loss of KCNQ1 mRNA and protein expression in stage II and III colon cancer has been proposed as a prognostic factor for poor disease-free survival 42. Additionally, another report showed that low expression of KCNQ1 protein was significantly associated with poor OS in patients with CRC with liver metastases after hepatic resection 43.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, genetic variation in ion channels and pumps that are involved in potassium homeostasis may also be associated with genes that have a role in cell proliferations and differentiation. The SCNN1B gene is associated with serum potassium 26 as well as gastric cancer 9 and the KCNQ1 gene, which provides information for potassium channels, 27 is also associated with the risk of colon, 28 colorectal, 29 and pancreatic cancer. 30 Also, a polymorphism in the KCNJ4 gene, which encodes another potassium channel, is associated with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…KCNQ1 is another tumor suppressor gene, and loss of its expression is considered to be an indicator of metastasis and poor prognosis [6163]. There is also evidence that the reduction in KCNQ1 expression in cancer cells may be mediated by promoter hypermethylation [62, 64].…”
Section: Discussionmentioning
confidence: 99%